2013
DOI: 10.2118/161875-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Petrophysical-Evaluation Method for Tight Formations From Drill Cuttings Only in the Absence of Well Logs

Abstract: The amount of tight-formation petrophysical work conducted at present in horizontal wells and the examples available in the literature are limited to only those wells that have complete data sets. This is very important. But the reality is that in the vast majority of horizontal wells, the data required for detailed analyses are quite scarce. Petrophysical evaluation in the absence of well logs and cores can now be considered owing to the possibility of measuring both the permeability and porosity of drill cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…A similar equation (Eq.1) that relates porosity and permeability to pore throat aperture was developed by Aguilera (2002): This equation is rigorously valid between 30 to 90% water saturation, but in practice we have been able to extend it beyond those limits with reasonable results for the tight formations we are studying in the GFREE research group (Aguilera 2002 andOrtega et al 2013). The porosity and permeability obtained from drill cuttings were used to estimate the pore throat radii (r p35 ) shown in Column 5 of Table 1.…”
Section: Pore Throat Aperture Radiimentioning
confidence: 93%
See 1 more Smart Citation
“…A similar equation (Eq.1) that relates porosity and permeability to pore throat aperture was developed by Aguilera (2002): This equation is rigorously valid between 30 to 90% water saturation, but in practice we have been able to extend it beyond those limits with reasonable results for the tight formations we are studying in the GFREE research group (Aguilera 2002 andOrtega et al 2013). The porosity and permeability obtained from drill cuttings were used to estimate the pore throat radii (r p35 ) shown in Column 5 of Table 1.…”
Section: Pore Throat Aperture Radiimentioning
confidence: 93%
“…In a recent work, Ortega et al (2012) concluded that in the absence of well logs and cores; complete petrophysical evaluation can now be considered a possibility owing to the fact that permeability and porosity can now be measured directly from drill cuttings. Ortega and Aguilera (2013) study was on vertical wells drilled in the tight gas Nikanassin group of the western Canada sedimentary basin (WCSB). The present study extends the work to that of a horizontal well where drill cuttings are available in the same geological area.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-five samples from 3095 to 3205 m were analyzed for determining porosity and permeability. Most of the samples were collected every 5 m. More details about the reservoir under consideration and the use of drill cuttings for formation evaluation have been published by Ortega and Aguilera (2013).…”
Section: Description Of Case Studymentioning
confidence: 99%
“…The methodology has been further extended so as to use data extracted from drill cuttings for quantitative formation evaluation including the estimation of irreducible water saturation (S wi ), true formation resistivity, porosity (or cementation) exponent m, the possibility of distinguishing between viscous and diffusion-like flow, and the construction of Pickett plots (Ortega 2012;Ortega and Aguilera 2013). In the Nikanassin Group of the WCSB considered in this study, there is no water leg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation